(untitled) - Dameron, Peggy (Orlando, Fla., 1988)
The joy of cooking naturally is not just another vegetarian cookbook. It is a course on a new way of cooking which will enable you to prduce festive dishes for special occasions and yet use only those natural ingredients which help promote better health.
Keywords: Vegetarian cooking,Nấu ăn chay